ANALISIS GEOTEKNIK DALAM PERENCANAAN KESTABILAN LERENG PADA OPERASI PENAMBANGAN BATU KAPUR DI PT. SBV – SUMATERA SELATAN - Ceni Febi Kurnia Sari (Jurnal Ilmiah Teknosains, 2020)
Geotechnics analysis is required to determine the geometric design of the mine’s slope stability, including the height and angle of the slope that is consid-ered safe. In general, the slope opening sand mine geometry is divided into two categories; overall slope and bench individual slope. Aside from calculat-ing the dimension of both slopes, the slope of dumping area is also being calculated.  Analysis and calculation of the slope stability is done at each drill-ing point location that represents the surrounding area and limited to maximum depth from each drilling point. Empirical analysis on calculating slope stability is needed to obtain safe overall slope and bench slope. In other words, slope stability analysis is needed to determine a slope to be stable enough to not endangering safety and wellbeing. Another directly related aspect to slope stability is to determine the Safety Factor. Safety Factor (SF) is an empirical value obtained from the restraining force divided by the driving force. The restraining force and the driving force acting on a slope are at least 2 (two) interrelated main factors, namely internal and external factors.